Experimental results from a linear wave power generator connected to a resonance circuit. Issue 4 (13th July 2012) - Ekergård, Boel; Boström, Cecilia; Hagnestål, Anders; Waters, Rafael; Leijon, Mats
Abstract : Abstract: The output voltage from a direct‐driven permanent magnet linear generator installed in a wave power plant varies both in amplitude and frequency. Electrical conversion is therefore necessary before grid connection can be achieved. The aim of this paper is to present an electrical conversion system based on the electric resonance phenomena. As one of the first steps in the development, and to gain further knowledge and understanding of the proposed resonance circuit, experimental tests with a single‐phase permanent magnet linear generator connected to a resonance circuit were performed. The experimental results presented in this paper indicated that a successful resonance between the generator and external circuit was achieved. The research regarding the wave energy converters lies within The Lysekil Wave Power Project at Uppsala University and has been ongoing since 2002. This article is categorized under: Wind Power > Science and Materials Energy Infrastructure > Systems and Infrastructure